SEROPREVALENCE OF TREPONEMA PALLIDUM INFECTION AMONG WOMEN WITH HISTORY OF MISCARRIAGE AND STILLBIRTH IN A FERTILITY HOSPITAL IN NNEWI, NIGERIA (Journal of Biomedical Investigation, 2022)
Background: Untreated sexually transmitted infections caused by spirochetes in pregnant females are associated with miscarriage and still-birth.Aim: This study was aimed at screening, confirming and investigating the seroprevalence of Treponema pallidum infection among women with history of miscarriage and still-birth in a private fertility hospital in Nnewi, Nigeria. Also, to assess the association between pregnancy outcome in relation to T. pallidum infection and determine the association between risk factor variables for T.pallidum infection among women with history of miscarriage and still birth in the study group.Methodology: This cross-sectional study involved 150 pregnant in- and outpatients of aged 20 to 49 years, randomly and who gave consent to participate. Treponema pallidum antibody was screened with serum using VDRL (Venereal Disease Research Laboratory) agglutination test and confirmed with Treponema palladium hemagglutination ELISA kit spectrophotometric method. Risk-factor variables investigated. Data analyzed using chi-square analysis with level of significance set at
Keywords: seroprevalence; Treponema pallidum; women; stillbirth; miscarriage; Nnewi